PENGERTIAN DAN KRITERIA MENETUKAN FASE PERKEMBANGAN: PENGERTIAN DAN KRITERIA MENETUKAN FASE PERKEMBANGAN - yurike bala; Radhitya Pakudu; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2021)
Development denotes a certain process, namely a process leading to future and not simply be repeated again. In personal development, there are changes that are more or less permanent and cannot be rotated return. Development refers to changes in a certain direction permanent in nature, such as brain growth not being found, not gaining weight, and body posture not experiencing development and so on